Assessment of essential oil as a potential anti-obesity agent: a narrative review. Issue 1 (2nd January 2017) - Rashed, Aswir Abd; Mohd Nawi, Mohd Naeem; Sulaiman, Kasmawati
Abstract: Several species of medicinal plants have long been used for the complementary treatment of obesity-diabetes in various systems of medicine. Among them are the plant-derived essential oils which are rich sources of volatile organic compounds. The objective of this review is to assess the effectiveness of essential oils as anti-obesity agents. All the literatures were extracted from three databases (PubMed, EBSCO Discovery Service and Ovid) from year 2000 to 2015 using the Medical subject heading (MeSH) terms 'essential oil', crossed with the term 'obesity', 'anti-obesity' or 'antiobesity'. Nine articles were selected and divided into five broad categories of experiments. The attenuation effects of essential oils on obesity may be mediated by several possible mechanisms that include anti-lipase activity, increasing the plasma glycerol concentration and suppressing fat accumulation. Only one randomized controlled trial (RCT) study on essential oil was identified so far and these data were not conclusive to provide evidence-based health claim on this issue.